Efficacy of Streptococcus agalactiae vaccine strains N3M and N4M in fry tilapia infected by different strains of S. agalactiae - Sukenda, Sukenda,; Firmansyah, Arif Lukman; Rahman, Rahman,; Nuryati, Sri; Hidayatullah, Dendi (Jurnal Akuakultur Indonesia, 2018)
ABSTRACT    Streptococcus agalactiae is a major bacterial streptococcosis disease that infects tilapia. This study aimed to analyze a specific and nonspecific immune system in fry tilapia that has been given with S. agalactiae vaccine from N3M and N4M strain and examine the protective immunity against S. agalactiae N3M, N4M, N17O, NK1,  and N14G strains infection. Fry tilapia used in this study has the weight of 7.086±0.948 g and length of 7.443±0.353 cm. The S. agalactiae strains that used were N3M, N4M, N17O, NK1,and N14G. Fry tilapia was vaccinated through intraperitoneal injection method with 0.1 mL per fish of N3M and N4M vaccines. Fish reared in aquarium sizing of 60×30×50 cm3 with a density of 10 fishes aquarium-1. Two weeks after vaccination, fry tilapia was tested with 0.1 mL fish-1 of each N3M, N4M, N17O, NK1, and N14G strains through intraperitoneal injection method. Antibody level measured with indirect enzym-linked immunosorbent assay (ELISA) method. The result of antibody level in vaccinated fish after vaccination of N3M, N4M vaccine, N3M and N4M control were 0.767; 0.743; 0.587; and 0.544, respectively. Relative percent survival in N3M vaccinated fish after challenged with N3M and N4M was 87.50% dan 64.70%, respectively, otherwise in N4M vaccinated fish was 62.50% dan 76.47%, respectively. N3M and N4M vaccine strain have better protection as only if it tested with similar bacteria strain. Keywords: formalin-killed cell, tilapia, protection, Streptococcus agalactiae, strains  ABSTRAK Streptococcus agalactiae merupakan bakteri utama penyakit streptococcosis yang menginfeksi ikan nila. Tujuan penelitian ini adalah menganalisis sistem imun spesifik dan nonspesifik pada benih ikan nila yang diberi vaksin S. agalactiae strain N3M dan N4M serta mengkaji imunitas protektif terhadap infeksi S. agalactiae strain N3M, N4M, N17O, NK1, dan N14G. Benih ikan nila yang digunakan memiliki bobot 7,086±0,948 g dan panjang 7,443±0,353 cm. Bakteri yang digunakan adalah S. agalactiae strain N3M, N4M, N17O, NK1,danN14G. Benih ikan nila divaksinasi menggunakan metode injeksi pada bagian intraperitoneal sebanyak 0,1 mL ekor-1 vaksin N3M dan N4M. Pemeliharaan dilakukan pada akuarium berukuran 60×30×50 cm3 dengan kepadatan 10 ekor akuarium-1. Dua minggu setelah vaksinasi benih ikan diuji tantang dengan strain bakteri N3M, N4M, N17O, NK1,  danN14G menggunakan metode injeksi pada bagian intraperitoneal dengan dosis 0,1 mL ekor-1. Level antibodi diukur dengan metode indirect enzym-linked immunosorbent assay (ELISA). Hasil menunjukkan level antibodi ikan setelah vaksinasi pada perlakuan vaksin N3M, N4M, kontrol N3M, dan kontrol N4M berturut-turut 0,767; 0,743; 0,587; dan 0,544. Kelangsungan hidup relatif ikan yang divaksin N3M setelah diuji tantang dengan strain N3M dan N4M berturut-turut 87,50% dan 64,70%, sedangkan pada ikan yang divaksin N4M berturut-turut 62,50% dan 76,47%. Vaksin strain N3M dan N4M memiliki proteksi lebih baik jika diuji tantang dengan strain bakteri yang sama. Kata kunci: formalin-killed cell, Streptococcus agalactiae, strain, proteksi, nila